225k views
2 votes
how do I solve for x intercepts of this equation. I'm having trouble solving it.
y = 2x ^(2) + 12x + 13

1 Answer

1 vote

y=2x^2+12x+13

To find the x-intercepts of this equation, substitute y by 0 at first


0=2x^2+12x+13

Now we need to factor this equation into 2 factors

We need 2 numbers their sum = 12 (the middle term)

But we can not find them mentally, then we will use the formula


x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

a is the coefficient of x^2

b is the coefficient of x

c is the numerical term

a = 2, b = 12, c = 13

Let us substitute them in the rule to find x


\begin{gathered} x=\frac{-12+\sqrt[]{(12)^2-4(2)(13)}}{2(2)} \\ x=\frac{-12+\sqrt[]{144-104}}{4} \\ x=\frac{-12+\sqrt[]{40}}{4} \end{gathered}

We will simplify the root


x=\frac{-12+2\sqrt[]{10}}{4}

Divide up and down by 2 to simplify the fraction


x=\frac{-6+\sqrt[]{10}}{2}

The 2nd root will be the same number but a different middle sign


x=\frac{-6-\sqrt[]{10}}{2}

The x-intercepts are


(\frac{-6+\sqrt[]{10}}{2},0)\text{and(}\frac{-6-\sqrt[]{10}}{2},0)

User TitanFighter
by
6.1k points